2022
DOI: 10.1159/000523942
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress, Hormones, and Neurodevelopmental Disorders

Abstract: Background: Early Life Stress (ELS) describes a broad spectrum of adverse and stressful prenatal events, namely prenatal maternal stress (PMS), or early postnatal events, which can have detrimental long-term influences on the physiology, cognition, and behavior of an individual. There is abundant evidence indicating that ELS exerts its lasting effects on the physical and mental health of the individual, likely acting through a number of mediating mechanisms, including the disruption of developmental programmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Prenatal stress has long been associated with an increased risk of various NDDs, most notably schizophrenia, ADHD and autism ( Ronald et al, 2011 ; Diz-Chaves et al, 2012 , 2013 ; Chan et al, 2018 ; Minakova and Warner, 2018 ; Makris et al, 2022 ). More recently, this association has been further characterized by changes in inflammatory biomarkers in the maternal circulation that may increase the risk of various NDDs.…”
Section: Factors To Consider In Rodent Models Of Maternal Immune Acti...mentioning
confidence: 99%
“…Prenatal stress has long been associated with an increased risk of various NDDs, most notably schizophrenia, ADHD and autism ( Ronald et al, 2011 ; Diz-Chaves et al, 2012 , 2013 ; Chan et al, 2018 ; Minakova and Warner, 2018 ; Makris et al, 2022 ). More recently, this association has been further characterized by changes in inflammatory biomarkers in the maternal circulation that may increase the risk of various NDDs.…”
Section: Factors To Consider In Rodent Models Of Maternal Immune Acti...mentioning
confidence: 99%
“…Autistic burnout may represent a distinct pathophysiological state resulting from allostatic overload, culminating in neurological and psychological dysregulation that leads to psychopathology. Previous work has described how allostatic load may interact with behavioral, psychosocial and physiological aspects of ASC (37)(38)(39)90); however, this model remains poorly characterized from a molecular perspective. Notably, the molecular mechanisms that mediate the association between ELS, CAS and psychopathology are also involved in ASC etiology.…”
Section: Early Life Stress Chronic Adolescent Stress and Allostatic L...mentioning
confidence: 99%
“…Here, we integrate recent characterizations of internal autistic experiences within a molecular framework to yield insight into psychopathology and suicidality in ASC. Interactions between psychosocial stress, ASC physiology and allostatic load have previously been proposed to influence clinical outcomes in autism (37)(38)(39). Singletary (37) proposed that autistic children are exposed to significant stress that could disrupt social and cognitive development during the early post-natal period.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study by Mikita et al, 2015 found that 10 to 16-year-old boys with high-functioning ASD exhibited greater levels of irritability than typically developing boys and showed marked changes in cortisol levels and heart rate in response to stressful stimuli [ 51 ]. This is because high levels of stress over a long period of time have been associated with high levels of cortisol in the body [ 52 ]. Therefore, in the future, the correlation of irritability with behavioral parameters and neurobiological indicators of stress in preschool children with irritability and features of neurodevelopmental disorders could be investigated and shown, as well as the differences in irritability and related neurological indicators in children with neurodevelopmental disorders compared to typically developing children.…”
Section: Discussionmentioning
confidence: 99%